Classification of rational surfaces of degree 11 and sectional genus 11 in P^4 - Graf von Bothmer, Hans-Christian; Ranestad, Kristian (MATHEMATICA SCANDINAVICA, 2009)
We use the BGG-correspondence to show that there are at most three possible Hilbert functions for smooth rational surfaces of degree 11 and sectional genus 11. Surfaces with one of these Hilbert functions have been classified by Popescu. The classification for a second one is done in this paper. For the third Hilbert function the classification is still open.